Max Weber and Value - Free Sociology / A Marxist Critique - Lawrence And Wishart; Lewis John (1975)
In this the writer examines Weber's weighty contribution, and asks how successful his concepts of ''value-free sociology'' and of the ''models'' of social structure have proved themselves to be for purposes of sociological analysis. Preface, Max Weber and Man and Fighter, Durkheim and the Group Mind, The Study of Cultures, The God of Things as They Are, Weber's Methodology, Capitalism: Its Origin and Nature, The House of Bondage, Talcott Parsons and Systems Theory, Conflict and Class, The Dimension of History, Evolution and Human Progress, Max Weber and Karl Marx, Consciousness and Social Change, The Making of History, Sociology and the Politics of Cultural Despair, Books, Authors Quoted or Mentioned.